2018
DOI: 10.26434/chemrxiv.5856825
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global and Local Reactivity Descriptors Based on Quadratic and Linear Energy Models for α,β-Unsaturated Organic Compounds

Abstract: <div>Global and local descriptors of chemical reactivity can be derived from conceptual density functional theory. Their explicit form, however, depends on how the energy is defined as a function of the number of electrons. Within the existing interpolation models, here, the quadratic and the linear energy model were used to derive global descriptors as the electrophilicity and nucleophilicity (defined as the negative of the ionization potential) and local descriptors employing either the corresponding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…In our previous study, we have shown that the condensed Fukui functions under the fragment molecular response (FMR) approach with the Hirshfeld-I partitioning method correctly describes the reactivity of α, β unsaturated systems as the crotonyl thioester. 33 Recently, our findings were further confirmed independently also by others. 34,35 Here, we use the validated local reactivity descriptor to analyze the crotonyl test system in different conformations and molecular environments as a vacuum, aqueous solution, and in the enzyme.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our previous study, we have shown that the condensed Fukui functions under the fragment molecular response (FMR) approach with the Hirshfeld-I partitioning method correctly describes the reactivity of α, β unsaturated systems as the crotonyl thioester. 33 Recently, our findings were further confirmed independently also by others. 34,35 Here, we use the validated local reactivity descriptor to analyze the crotonyl test system in different conformations and molecular environments as a vacuum, aqueous solution, and in the enzyme.…”
Section: Introductionsupporting
confidence: 86%
“…The reactivity of the crotonyl thioester as the enzyme substrate model was studied with local reactivity descriptors based on conceptual DFT as the Fukui function [11][12][13] within the linear energy model. The chosen approximations for the Fukui function and the method to condense it to atoms were validated in our previous study on the electrophilicity and nucleophilicity of α, β unsaturated esters, amides, and thioesters 33 and are summarized here briefly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivity of the crotonyl thioester as the enzyme substrate model was studied with local reactivity descriptors based on conceptual DFT as the Fukui function [11][12][13] within the linear energy model. The chosen approximations for the Fukui function and the method to condense it to atoms were validated in our previous study on the electrophilicity and nucleophilicity of α, β unsaturated esters, amides, and thioesters 33 and are summarized here briefly.…”
Section: Methodsmentioning
confidence: 99%
“…32 From conceptual DFT, we used the global electrophilicity descriptor ω and nucleophilicity descriptor N, as well as the corresponding local nucleophilicity and electrophilicity descriptors ℓN and ℓω. 33 These electronic features were complemented with atomic charges (q) from the DDEC6 scheme 34 and the electrostatic potential at the nuclei (VN) of the reactive atoms. 35 In terms of sterics and dispersion, we use the ratio of solvent accessible surface area (SASAr) 36 of the reactive atoms and the universal quantitative dispersion descriptor Pint.…”
Section: Reaction Feature Generationmentioning
confidence: 99%